Pengamanan Dokumen Digital Perusahaan Menggunakan Metode Least Significant Bit (LSB) Dan Algoritma RC4 Stream Chipher - Handa Gustiawan; Hesti Rian (Jurnal Teknologi Informatika dan Komputer, 2022)
In today's digital era, where company documents are made in digital form, the issue of security and confidentiality of data or documents is an important aspect for companies. Steganography is a technique to hide messages or secret data in a place called a carrier file. While cryptography is a science that studies how to keep data or messages safe when sent, from sender to recipient without interference from other parties. The purpose of this study is to provide maximum security for company digital documents, using the Least Significant Bit (LSB) steganography method and the RC4 stream cipher cryptographic algorithm. The expected result of this research is to produce an application that can secure the company's digital documents